2020
DOI: 10.1021/acssuschemeng.9b05615
|View full text |Cite
|
Sign up to set email alerts
|

Manganese Nanoparticles Control Salinity-Modulated Molecular Responses in Capsicum annuum L. through Priming: A Sustainable Approach for Agriculture

Abstract: The application of nanomaterials as a method to overcome plant stress and increase crop yield is relatively new as compared to the use of fertilizers and pesticides in agricultural production. In the present study, manganese (III) oxide nanoparticles (MnNPs) were investigated as a nanopriming agent to alleviate salinity stress in Capsicum annuum L. during germination at 100 mM NaCl. In general, the root growth in both nonsalt and salt-stressed seedlings was significantly improved by MnNPs (0.1, 0.5, 1 mg/L). S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(95 citation statements)
references
References 53 publications
2
92
0
1
Order By: Relevance
“…A previous study reported that MnO-NPs had no considerable impact on seed germination [ 33 ]. However, they improved the seedling growth in lettuce and increased root growth in Capsicum annuum L. [ 33 , 39 ]. We also investigated the effects of the different MnO-NPs priming treatments on seedling growth in the diploid and triploid varieties ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A previous study reported that MnO-NPs had no considerable impact on seed germination [ 33 ]. However, they improved the seedling growth in lettuce and increased root growth in Capsicum annuum L. [ 33 , 39 ]. We also investigated the effects of the different MnO-NPs priming treatments on seedling growth in the diploid and triploid varieties ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The ZnO-NPs obtained using the duckweed extract showed a smaller average size than those reported in other studies [ 4 , 20 , 22 ]. It is well known that the size of NPs strongly depends on the chemical composition, classes, and amounts of metabolites contained in the biological entities [ 10 , 11 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…As for the shape of the biogenic ZnO-NPs, a wide variability can be observed depending on the biological entity used to carry out the biogenic syntheses. Such an effect is very frequently noted, and it mainly depends on the chemical composition of the plant extract [ 10 , 11 ]. For instance, some previous studies on plant biogenic synthesis evidenced as ZnO-NPs of flower or hexagonal shape can be obtained using Carissa edulis , Justicia spicigera and Medicago sativa [ 20 , 21 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoparticles (NPs) such as AgNPs and Fe 2 O 3 were documented to improve seed development by enhancing starch metabolism and triggering Fe acquisition in wheat and rice [10]. Seed priming in lupine with ZnO NPs played an important role in NaCl stress tolerance via enhancing antioxidant activities and Na + adjustment [11]. Similarly, in wheat crops, AgNPs modulated hormonal balance while improved seed germination and salinity tolerance [12].…”
mentioning
confidence: 99%